EFFECT OF SHADING, GIBBERELLIC ACID AND MICRONUTRINTS ON SOME CHEMICAL COMPOSITION CHARACTERS OF INDIAN RUBBER PLANT Ficus elastica Roxb. var. decora - Asmaa Al-Layla; Omar Aatrakchii; Salim Alsultan (Mesopotamia Journal of Agriculture)
This study was carried out in a private nursery in Mosul city, between February and September 2004, to investigate the effect of shading percentage, GA3 and micronutrient on chemical composition of Indian rubber plant Ficus elastica Roxb. decora plants produced by vegetative propagation. Hence, three different factors were investigated: shading at 35 and 70% from natural light, spraying with gibberellic acid (GA3) at 0, 100, 200 and 300 mg/ Liter were applied every 21 days, two times as foliar spray, and micronutrient at 0, 1 and 2 dosage/ week/ pot. The Factorial Experiment was conducted by using the Split-plot in Randomized Complete Block Design. Each treatment was replicated three times. The results can be summarized as follows: The shading percentage had no effect on all chemical characters studied except Fe content. Spraying with 300 mg GA3/ Liter gave a significant increase in total chlorophyll, total N % and the content of Zn, Cu and Mn when compared with the control plants, but these treatments caused a significant decrease in Fe content in leaf tissue, while carbohydrate content did not affect. Fertilization with micronutrient increased the content of anthocyanine, Zn and Cu increased to 7.19 mg/ 100g fresh weight, 79.06 mg/ kg, 14.32 mg/ kg, respectively when adding 2 dosages of micronutrient/ week/ pot compared with 6.31 mg/ 100 gm fresh weight, 71.38 mg/ kg and 10.59 mg/ kg for control respectively. In general, the interaction between 35% shading, spray with 300 mg GA3/ Liter and one dosage of micronutrient gave best results of N% and CHO%, but the best results of total chlorophyll and Anthocyanine content were in 2 dosage micronutrient/ week. Finally, higher values of Zn, Cu and Mn content were under the interaction 70% shading, 200 mg GA3 / Liter and 2 dosage of micronutrient.